Reclamation of Wasteland through Different Vegetative Interventions - Kumar, Ashok; Kumar, Vikas; Bish, Hemlata; Kumar, Rahul (Indian Forester, 2015)
The reclamation of wasteland and development measures in general includes land clearing, soil and water conservation, enhancing nutrient status, provision of irrigation facilities and so on. However, the existing status of wastelands shows wide variation across different regions of the country in terms of their suitability for cultivation. Therefore, it is necessary to carry out a scientific assessment of the existing status; fertility, erosion levels, soil conditions, water potential, suitable cropping system, etc. of the waste lands spread over different agro-climatic zones of the state so as to prepare a realistic reclamation-cum-development plan for the wastelands. Thus rehabilitation of the wasteland through the sustainable management serves as a better cover to the soil and aids regeneration of forests.